Pheochromocytoma with Type 2 Diabetes Mellitus and Subclinical Cushing's Syndrome - Rosyid Mawardi; Sony Wibisono Mudjanarko; Elvina Yunasan (Wolters Kluwer - Medknow Publications, 2023)
Pheochromocytoma is a catecholamine-producing tumor that originates from adrenal medullary chromaffin cells. It affects 1-8 per million people annually and accounts for 5% of adrenal incidentalomas. Here, we report a 62-year-old man with sudden excessive sweating, palpitations, and headaches. He has a history of type 2 diabetes mellitus, hypertension, and an adrenal mass found incidentally by ultrasonography. Clinical history and further imaging suggest a pheochromocytoma; however, the presence of subclinical Cushing's syndrome and a normal urine vanillylmandelic acid level have led to diagnostic challenges. Finally, the patient underwent a left adrenalectomy. Histopathology showed the tumor as thick nests of cells, positive chromogranin A staining, and negative inhibin staining that confirmed the diagnosis of pheochromocytoma. In conclusion, our patient had pheochromocytoma that was thought to produce adrenocorticotropic hormone ectopically, resulting in subclinical Cushing's syndrome.